SYSTEMATIC RISK, DEPOSIT, EFFICIENCY, AND INTEREST RATE ON BANKING’S PERFORMANCE - Cynthia Agustin; Ellen Rusliati (Jurnal Riset Bisnis dan Manajemen, 2020)
This study aims to analyze the effect of systematic risk, deposit, level of efficiency, and interest rate on Sharia Banking’s performance listed in Indonesian Stock Exchange (IDX) for the period of 2014-2017. The analysis technique used in this study is descriptive and verificative approach, by using panel data regression. The population are all Sharia Banks listed in IDX for the period of 2014-2017 by using saturated sample. The result showed that the systematic risk, deposit, level of efficiency and interest rate effected significantly on the Sharia Bank’s financial performance. Partially, systematic risk effected negatively significantly, deposit and interest rate effected positive but insignificantly, level of efficiency effected positive significantly on Sharia Bank’s financial performance.